Empirical Research on Occupational Adaptation of Graduates from Higher Vocational Colleges and Educational Considerations (Global Journal of Human-Social Science, 2019)
Through empirical research this paper puts forward and validates the theoretical model of occupational adaptation for vocational college graduates which consists of four dimensions occupational cognitive adaptation occupational psychological adaptation occupational skills adaptation interpersonal and professional environment adaptation The study finds that the overall level of occupational adaptation of graduates from higher vocational colleges is low occupational adaptation is affected by years of graduation and income satisfaction level occupational psychological adaptation is affected by years of graduation unit property and income satisfaction level interpersonal and professional environment adaptation is affected by income satisfaction level Therefore higher vocational colleges need to deepen the work of vocational guidance improve the training mode of talents in higher vocational colleges strengthen the mental health education of students in colleges and guide students to establish correct values
Keywords: higher vocational college; graduates; occupational adaptation; education